1996
DOI: 10.1046/j.1526-4610.1996.3610608.x
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Headache is an Inherited Disorder in Some Families

Abstract: We investigated the familial occurrence of cluster headache in 370 probands with cluster headache, diagnosed according to the operational diagnostic criteria of the international Headache Society. Seven probands belonged to three families. A positive family history of cluster headache was found in 7% (25 of 366) of the families. Compared with the general population, the first- and second-degree relatives of the 370 probands with cluster headache had a 14- and 2-fold increased risk of having cluster headache, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 11 publications
1
32
0
1
Order By: Relevance
“…Primary headaches, such as migraine 42 and cluster headache, 43 have a significant genetic predisposition, and the tumor may trigger that predisposition to manifest. The family history data are consistent with a predisposed individual being exposed to a milieu that is pronociceptive and, thus, developing headache.…”
Section: Commentmentioning
confidence: 99%
“…Primary headaches, such as migraine 42 and cluster headache, 43 have a significant genetic predisposition, and the tumor may trigger that predisposition to manifest. The family history data are consistent with a predisposed individual being exposed to a milieu that is pronociceptive and, thus, developing headache.…”
Section: Commentmentioning
confidence: 99%
“…It seems logical to suppose that all the primary headaches have a predisposition that is in some way activated. Certainly this has been suggested for cluster headache [35,65], and we have recently seen it suggested for both familial paroxysmal hemicrania and familial SUNCT! Overall it seems a good way to understand primary headache.…”
Section: Genetics Of Headachementioning
confidence: 81%
“…This figure probably overestimates the true familial occurrence of cluster headache, as we did not personally confirm the diagnosis in relatives, and some cluster headache sufferers will mistake migraine in relatives for cluster. 14 Nevertheless, Russell et al 14 did find that first degree relatives of cluster headache patients had a fourteen-fold risk of cluster headache as compared to the general population. Kudrow and Kudrow found that 12% of cluster women and 10% of cluster men had at least one first degree relative with cluster headache.…”
Section: Clinical Featuresmentioning
confidence: 99%